Evaluation of organic molecules originated during composting process - Bernabe, Giseli Aparecida [UNESP]; Almeida, S. [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer, 2011)
The composting process using sugarcane bagasse, animal manure, and urea as source of organic matter, microorganism, and nitrogen, respectively, were evaluated regarding the thermal behavior considering the maturation period: 0 (raw), 15, 22, 30, and 60 days. Thermogravimetric and differential thermal analysis curves were obtained in a synthetic air atmosphere and heating rate of 10 A degrees C min(-1) in the range of 30-600 A degrees C. The raw compost showed 80% organic matter, which was reduced up to 58% to 60 days compost. Two main mass losses were verified, corresponding to characteristics exothermic peak in differential thermal analysis curves depending on the maturation period. The variation in organic composition was evaluated by Fourier transform infrared spectroscopy verifying the structures (lignin, cellulose, and hemicelluloses) changes with composting process, and the gas chromatography-mass spectrometry was used to identify substance soluble in hexane.
Keywords: Sugarcane bagasse; Composting process; Thermal behavior; GC-MS